Root-knot Nematodes - Perry, Roland N (CABI, 2014)
Among plant-parasitic nematodes, the root-knot nematodes (Meloidogynespp.) are the most economically important group. They have a worldwide distribution and are obligate parasites of the roots, tubers and corms of thousands of plant species, resulting in devastating adverse effects on the quality and yield of crops. They are especially prevalent in the warm temperate and tropical regions where subsistence agricultural systems predominate. Thus, root-knot nematodes have major financial and social impacts and have been the subject of extensive research, including studies on taxonomy, biology, plant–nematode interactions and, especially, control approaches. This research, undertaken over many years, has generated an enormous volume of literature. A summary of the research is needed and, while it is impossible to reference all relevant literature, it is important to condense and focus on the main findings. This is the first aim of the present volume. The second aim is to reflect the exciting and recent advances in the molecular genetics of rootknot nematodes. With the elucidation in 2008 of the genomic sequences of M. haplaand M. incognita, it will be possible to perform comparative genomic studies with free-living and animal-parasitic nematode genomes. This will provide not only an insight into aspects of the development and the features of obligate parasitism but also a basis for in-depth analysis of the characteristics implicit in a life strategy that has to cope with the vagaries of the parasitic existence. A comparison of these two Meloidogyne species will also provide information on the differences between an organism reproducing in an asexual manner compared with one reproducing sexually. A third aim of this book is to highlight the control options and management strategies, especially in the light of an understanding of the biology of the genus as a whole and of the important differences between individual species. The changing control scenarios reflect reduction in the use of chemical control strategies and the concomitant increasing importance of biological management and resistance mechanisms. The increasing relevance of plant biotechnology and other management options will be central to the future control of Meloidogynespecies. Global warming is likely to result in increased spread of tropical species to regions and crops that hitherto have been unaffected, so targeting of environmentally acceptable control strategies based on a sound knowledge of nematode biology is essential.